Design, fabrication and testing of a bicycle operated duplex pump - ASHOK KUMAR, V. M; Lal, C. L; Mohanan, C. K; Subha Rani Kurian (Tavanur Kelappaji College of Agricultural Engineering and Technology, 1990)
project report
project report
Keywords: project report